The role of SPAG1 in the assembly of axonemal dyneins in human airway epithelia - Smith, Amanda J.; Bustamante-Marin, Ximena M.; Yin, Weining; Sears, Patrick R.; Herring, Laura E.; Dicheva, Nedyalka N.; López-Giráldez, Francesc; Mane, Shrikant; Tarran, Robert; Leigh, Margaret W.; Knowles, Michael R.; Zariwala, Maimoona A.; et al. (Journal of cell science, 2022)
Mutations in SPAG1, a dynein axonemal assembly factor (DNAAF) that facilitates the assembly of dynein arms in the cytoplasm before their transport into the cilium, result in primary ciliary dyskinesia (PCD), a genetically heterogenous disorder characterized by chronic oto-sino-pulmonary disease, infertility and laterality defects. To further elucidate the role of SPAG1 in dynein assembly, we examined its expression, interactions and ciliary defects in control and PCD human airway epithelia. Immunoprecipitations showed that SPAG1 interacts with multiple DNAAFs, dynein chains and canonical components of the R2TP complex. Protein levels of dynein heavy chains (DHCs) and interactions between DHCs and dynein intermediate chains (DICs) were reduced in SPAG1 mutants. We also identified a previously uncharacterized 60 kDa SPAG1 isoform, through examination of PCD subjects with an atypical ultrastructural defect for SPAG1 variants, that can partially compensate for the absence of full-length SPAG1 to assemble a reduced number of outer dynein arms. In summary, our data show that SPAG1 is necessary for axonemal dynein arm assembly by scaffolding R2TP-like complexes composed of several DNAAFs that facilitate the folding and/or binding of the DHCs to the DIC complex.